200. The Utility of a Rapid Multiplex PCR Assay in the Management of Staphylococcus Aureus Bacteremia at a Tertiary Care Center. (15th December 2022) - Gholami, Sherry; Chundi, Vahini; Fan, Katherine; Duong, Lan; Kumar, Princy N; Timpone, Joseph G
Abstract: Background: Staphylococcus aureus bacteremia (SAB) is a major cause of community and healthcare-acquired bacteremia and is associated with a high burden of morbidity and mortality. Appropriately tailoring management based on methicillin sensitivity can help minimize unnecessary administration of broad-spectrum antibiotics and ensure adequate treatment of MSSA/MRSA. The Verigene® (Luminex Corporation) is a multiplex PCR assay that provides rapid identification of bloodstream pathogens. We performed a QI project to determine the utility of this assay in managing patients with SAB. Methods: We performed a single-center retrospective cohort study of positive SAB cultures from May 2020 to May 2021. Electronic health record review was conducted to abstract patient demographics, clinical characteristics, outcomes, blood culture data, and antibiotic management. Statistical analysis was done with the unpaired t-test and fishers exact test to identify associations of statistical significance. Results: We identified 97 cases of SAB: 66% MSSA (n = 64), 34% MRSA (n = 33). Patient characteristics included: mean age 61 years, 58.8% male, 42% immunocompromised, 83.5% with ID consult, 38.1% with ICU admission, mean length of stay 20.3d, and 24.7% mortality. Using the Verigene® assay, we noted 2.6% discordance with standard microbiological technique (n = 2). The timing of Verigene® results and provider response were as follows: Variable Mean (SD) n Time to Verigene ® report from culture collection (hrs) 26.2 (12.2) 92 Time to final report from culture collection (hrs) 82.2 (25.2) 97 Time to ordering new MSSA-targeted agent from Verigene ® report (hrs) 65.7 (41.6) 40 The mean duration of SAB was 3.1d (MSSA = 2.8d, MRSA = 3.6d, p = 0.2477). There was a statistically significant difference in patient mortality with respect to methicillin sensitivity status: MSSA 15.6%, MRSA 42.4%, p = 0.0075, as well as mortality with ID consult 19.8% versus no ID consult 50%, p = 0.0223. Conclusion: Despite the incorporation of a rapid multiplex PCR assay to detect bloodstream infections, the time to de-escalation for MSSA was sub-optimal (2.7 days). ID consultation continues to be an important component of SAB management as it improves patient outcomes and contributes to education of healthcare providers. Disclosures: Lan Duong, PharmD, Johnson & Johnson: Stocks/Bonds|Lilly USA: Stocks/Bonds|Novavax: Stocks/Bonds Princy N. Kumar, MD, American Gene Technologies: Grant/Research Support|BioHaven: Grant/Research Support|Eli Lilly: Grant/Research Support|Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Gilead: Stocks/Bonds|GSK: Grant/Research Support|GSK: Stocks/Bonds|Johnson&Johnson: Advisor/Consultant|Johnson&Johnson: Stocks/Bonds|Merck: Advisor/Consultant|Merck: Grant/Research Support|Merck: Stocks/Bonds|Moderna: Stocks/Bonds|Pfizer: Stocks/Bonds|Regeneron: Grant/Research Support|TheraTechnologies: Grant/Research Support|ViiV: Advisor/Consultant Joseph G. Timpone, Jr., MD, Gilead: Stocks/Bonds|Merck: Stocks/Bonds.